1995
DOI: 10.1083/jcb.129.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Cellubrevin and synaptobrevins: similar subcellular localization and biochemical properties in PC12 cells.

Abstract: Abstract. There is strong evidence to indicate that proteins of the synaptobrevin family play a key role in exocytosis. Synaptobrevin 1 and 2 are expressed at high concentration in brain where they are localized on synaptic vesicles. Cellubrevin, a very similar protein, has a widespread tissue distribution and in fibroblasts is localized on endosome-derived, transferrin receptor-positive vesicles. Since brain cellubrevin is not detectable in synaptic vesicles, we investigated whether cellubrevin and the synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 64 publications
(93 reference statements)
9
75
2
Order By: Relevance
“…As expected, Ca 2Ï© -dependent secretion of hGH was decreased (to 32% of control) by the presence of botB/LC in cells transfected with a plasmid containing wild-type syb2 ( Figure 5B). Such profound, but incomplete inhibition of release has been described previously (Chilcote et al, 1995;Quetglas et al, 2002). The expression of botB/LC-resistant syb2(Q76V,F77W) restored secretion (104% of control) in the presence of toxin ( Figure 5B).…”
Section: Syb2 Dimerization Mutants Are Unable To Support Secretionmentioning
confidence: 67%
“…As expected, Ca 2Ï© -dependent secretion of hGH was decreased (to 32% of control) by the presence of botB/LC in cells transfected with a plasmid containing wild-type syb2 ( Figure 5B). Such profound, but incomplete inhibition of release has been described previously (Chilcote et al, 1995;Quetglas et al, 2002). The expression of botB/LC-resistant syb2(Q76V,F77W) restored secretion (104% of control) in the presence of toxin ( Figure 5B).…”
Section: Syb2 Dimerization Mutants Are Unable To Support Secretionmentioning
confidence: 67%
“…VAMP3 binds to plasma membrane t-SNAREs syntaxin1, syntaxin4, SNAP-23 and SNAP-25 [22,29,30,34]. Using the cell fusion assay in the current study, we examined the membrane fusion capacity of the ternary complexes formed by VAMP3 and the plasma membrane t-SNAREs.…”
Section: Resultsmentioning
confidence: 99%
“…VAMP3 forms complexes with syntaxin1, syntaxin4, SNAP-23 and SNAP-25 [29][30][31]. It has been reported that VAMP3 forms ternary complexes with syntaxin4/SNAP-25 [22] and syntaxin4/SNAP-23 [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyclonal rabbit antibodies against mouse L1 and Fab fragments generated from this antibody were described previously (Rathjen and Rutishauser, 1984). The polyclonal anti-Syb 2 antibody (MC23) was described previously (Chilcote et al, 1995). The following commercial antibodies were used in this study: monoclonal anti-Na/K-ATPase a-1 (clone C464.6) from Upstate Biotechnology (Charlottesville, VA), monoclonal antisyntaxin 13 (clone 15G2) from StressGen (San Diego, CA), and monoclonal anti-Vti1b (Transduction Laboratories clone 7) from BD Biosciences (Franklin Lakes, NJ).…”
Section: Antibodies Clones and Reagentsmentioning
confidence: 99%